Serum phospholipase A2 and phosphoglycerate kinase 1 levels for prognostic assessment of endocrine therapy in elderly patients with prostate cancer - CAI Chunjie, ZHANG Jin (Zhongguo linchuang yanjiu)
Objective：To investigate the prognostic assessment value of serum phospholipase A2(PLA2) and phosphoglycerate kinase 1(PGK1) levels in elderly patients with prostate cancer undergoing endocrine therapy. Methods： A total of 106 elderly patients with prostate cancer who underwent endocrine therapy at Suzhou Science and Technology City Hospital from June 2021 to June 2023 were selected as the observation group. Additionally, 60 healthy elderly individuals undergoing physical examination were set as the control group. Serum levels of PLA2 and PGK1 in all subjects were measured using enzyme-linked immunosorbent assay (ELISA). Univariate and multivariate logistic regression analyses were used to identify factors affecting the prognosis of endocrine therapy. Results： Compared with the control group, the observation group had significantly higher serum levels of PLA2 ［(34.75±1.26)ng/mL vs (4.58±1.02)ng/mL,t=158.353,P＜0.01］ and PGK1 ［(10.69±0.36)ng/mL vs (1.54±0.07)ng/mL, t=194.561,P＜0.01］. Multivariate logistic regression analysis indicated that serum levels of PLA2, PGK1, and TNM staging of the tumor were independent prognostic factors for the efficacy of endocrine therapy in elderly patients with prostate cancer (P＜0.05). Conclusion： Serum levels of PLA2 and PGK1, along with TNM staging of the tumor, can predict the prognosis of elderly patients with prostate cancer undergoing endocrine therapy and have high predictive value.